European Standards Implementation in the Area of Occupational Health and Safety in Polish Enterprises - Boczkowska, Katarzyna; Znajmiecka-Sikora, Marta (Wydawnictwa Politechniki Łódzkiej, 2016)
The aim of the study is to analyze how Polish employers fulfill their responsibilities in terms of providing safe and healthy working conditions, including: standards for risk assessment, and adaptation of machinery to legal requirements. The research was conducted by questioning 2000 economic entrepreneurs and based on the results from the questionnaire prepared by the expert team. The results prove that, despite the adjustment of Polish law to EU standards, Polish employers still do not adequately fulfill their obligations in terms of occupational health and safety . Moreover, the study shows that implementation of the OSH management system supports the implementation of existing legislation related to safety at work.
Keywords: Normy EN; Bezpieczeństwo i higiena pracy; Maszyny i urządzenia; Metodologia badań; przedsiębiorstwo; European standards (EN); Health and safety at work; Machinery and equipment; Research methodology; Enterprises